Introduction to information systems : an internetworked enterprise perspective - O'Brien, James A. (Boston : Irwin/McGraw-Hill, 1998)
Business
2003-01-21
Keywords: Information systems; Management information systems; Informatin technology; Business enterprises-Communication systems; Database management; Global management